A Compliant Actuator-Sensor Unit using a Shape Memory Alloy and Capacitive Force Sensing for Active Exoskeleton Interfaces - Fischer, Nikola; Alagi, Hosam; Beigl, Michael; Hein, Bjorn; Mathis-Ullrich, Franziska (IEEE-RAS International Conference on Humanoid Robots, 2023)
Robotic lightweight-exoskeletons show great potential to enhance human motion capabilities for the disabled, elderly, and healthy. Active human-robotic interfaces with integrated actuation and sensing allow high quality measurements and an optimal fit when worn. We present a compact Compliant Actuator-Sensor Unit (CASU) that can be embedded in most interfaces. Based on shape memory alloy strips in a compliant parallel configuration, this actuator-sensor unit is able to provide a controllable force impact. The sensing of interaction forces through the user's clothing is enabled using a thin layer based capacitive force sensor. The unit was characterized in a test setup and attached to a subject's limb. We could demonstrate controllable actuation in the force range of up to 62 N with effective force offsets of 13.7 N from arbitrary contact force requiring less than 10 W. The unit showed reliable sensing, revealing characteristic patterns of basic limb movements. The actuation controls the initial contact forces and enables robust interaction force monitoring and can thereby facilitate further signal processing. For future work, we will miniaturize the unit further and investigate compensation of interface displacements during activities of daily living in a user study.
CRIS-Team Scopus Importer:2024-12-16